The Practicality and Effectiveness of the E-Worksheet with Creative Inquiry Based and HOTS Oriented “3D PageFlip” for Online Learning - I wayan distrik; Chandra Ertikanto; Feriasyah Sesunan (Jurnal Pembelajaran Fisika, 2022)
Most students experienced difficulties in understanding electricity learning materials in online learning because this was delivered asynchronously without observation/investigation and interaction with its learning environment. To overcome this problem, a teaching material that is able to deliver natural facts and phenomena to display in one place/space, the Electronic Student’s Working Sheet (ESWS) with 3D PageFlip is required. Material elaboration in this ESWS follows creative inquiry syntax with an orientation to the higher order of thinking skill (HOTS). The objective of this research was to describe the practicality and effectiveness of the ESWS with Creative Inquiry-Based and HOTS Oriented 3D PageFlip for online learning in improving self-efficacy and communication skills. This research used a static one-group pretest-posttest design. The research population was students in Public Senior High School 1 in Airnaningan, Tanggamus district, Lampung province. Two classroom samples were taken with cluster random sampling. Samples were divided into experiment and control groups. The experiment classroom was taught by using the ESWS with creative inquiry-based and HOTS oriented 3D PageFlip and the control group was taught by using a regular student’s working sheet containing questions and problems for exercises. Data were analyzed descriptively to describe self-efficacy understanding and communication skills. The differences in self-efficacy understanding and communication skills between experiment and control classrooms were analyzed with an independent sample t-test. The research result showed that the ESWS with creative inquiry-based and HOTS oriented 3D PageFlip was practical to use in physics learning with an average implementation score of 87.03 and with very positive students’ responses (94.44%). The ESWS with creative inquiry-based and HOTS oriented 3D PageFlip was also effective in improving self-efficacy and communication with n-gains of 0.77 and 0.80 respectively and they belonged to the high n-gain category.Keywords: Practicality, Effectiveness, CommunicationDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202201